Novel Mechanisms for Post-Transplant Maintenance Therapy in Acute Myeloid Leukemia - Manobianco, Steven A.; Rakiewicz, Tara; Wilde, Lindsay; Palmisiano, Neil D. (Frontiers in Oncology, 2022)
Allogeneic stem cell transplantation has improved survival for patients with acute myeloid leukemia (AML), especially for patients with disease at high risk of relapse. However, relapse remains the most common cause of treatment failure and death in the post-transplant period. Maintenance therapy, an extended course of treatment after achieving remission to reduce the rate of relapse, is an important component of the treatment of various hematologic malignancies; however, its role in the treatment of AML is far less well-defined. Recently, there has been significant interest in the use of novel therapeutic agents as maintenance therapy after allogeneic stem cell transplant, utilizing new mechanisms of treatment and more favorable toxicity profiles. In this review, we will discuss the mechanistic and clinical data for post-transplant maintenance therapies in AML. Then, we will review several emergent and current clinical trials which aim to incorporate novel agents into maintenance therapy regimens.